2014
DOI: 10.1039/c4cc04283b
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise π-extension of meso-alkylidenyl porphyrins through sequential 1,3-dipolar cycloaddition and redox reactions

Abstract: Several regioselectively π-extended, pyrrole fused porphyrinoids have been synthesized by the 1,3-dipolar cycloaddition of meso-alkylidene-(benzi)porphyrins. Pd(II) complexes gave oxidation resistant, bis-pyrrole fused adducts. The repeated 1,3-dipolar cycloaddition followed by oxidation-reduction of pentaphyrin analogs afforded π-extended porphyrin analogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This in turn could be oxidized with DDQ to afford the pyrrole-fused benzipentaphyrin 505 . A further cycloaddition–oxidation sequence afforded a dipyrrolo benzipentaphyrin (not shown) …”
Section: Benziporphyrins Heterobenziporphyrins and Related Systemsmentioning
confidence: 99%
“…This in turn could be oxidized with DDQ to afford the pyrrole-fused benzipentaphyrin 505 . A further cycloaddition–oxidation sequence afforded a dipyrrolo benzipentaphyrin (not shown) …”
Section: Benziporphyrins Heterobenziporphyrins and Related Systemsmentioning
confidence: 99%
“…Similarly, thiophene dicarbinol 122b reacted with 121 to give thiabenziporphyrin 123b in 8% yield and an expanded product 124b in 1% yield. 72 In addition, condensation of naphthitripyrrane 126 with thiophene dicarbinol 122b in the presence of TFA, followed by oxidation with DDQ, gave a naphthiporphyrin system 127 with two exocyclic double bonds (Scheme 55). The X-ray structure of 123a showed that the ring system is severely puckered and the benzene subunit lies virtually at right angles to the rest of the macrocycle.…”
Section: Benziporphyrins With Exocyclic Double Bondsmentioning
confidence: 99%
“…71 Benziporphyrin 123c and the corresponding palladium(II) complex 123d have been shown undergo 1,3-dipolar cycloadditions with an azomethine ylide to give extended structures (Scheme 53) and similar chemistry was reported for benzipentaphyrin 125b. 72 In addition, condensation of naphthitripyrrane 126 with thiophene dicarbinol 122b in the presence of TFA, followed by oxidation with DDQ, gave a naphthiporphyrin system 127 with two exocyclic double bonds (Scheme 55). 73 As would be expected, none of these macrocycles exhibit aromatic properties.…”
Section: -Hydroxybenziporphyrinsmentioning
confidence: 99%
“…The azomethine ylide (prepared in situ by reaction of sarcosine and paraformaldehyde) reacted with meso-diethylmalonylidene-(m-benzi)pentaphyrin affording the pentaphyrin chlorin-type analog 114 in 49% yield (Figure 23). 95 After an oxidation step of the pyrrolidine ring, followed by reduction of the macrocycle with NaBH4, the resulting product was submitted to another 1,3-dipolar cycloaddition under the same conditions to afford the chlorin-type derivative 115 in 75% yield. The π-system delocalization can potentially be improved by submitting compound 115 to a new sequential oxidation and reduction protocol, affording a new derivative bearing two fused pyrrole-type moieties.…”
Section: Porphyrinoids In Cycloaddition Reactionsmentioning
confidence: 99%
“…Lee and co-workers 95 extended the 1,3-dipolar cycloaddition approach of azomethine ylides to prepare Pd(II) complex (benzi)chlorin 111 from the reaction of the precursor 110 and the azomethine ylide generated in situ at 90 °C in toluene for 1 h under N2. The bacteriochlorin-type derivative 112 was also isolated as a diastereomeric mixture in 39% yield, being obtained as the chlorin-type analog but only in vestigial amounts.…”
Section: Author(s)mentioning
confidence: 99%